Forest liquidation, rural agrarian poverty and growth in Nigeria (2021)
This paper assesses forest resource liquidation within the context of rural agrarian poverty and growth in Nigeria, using annual and quarterly data from 1990 to 2016, and 2001 to 2019. Descriptive statistics and correlation analysis were employed to examine how forest resource utilisation is associated with rural agrarian poverty and economic growth. Findings revealed that forest resources have consistently been exploited in an unrestrained manner in the last 26 years, with shifting agriculture and urbanisation as major drivers. In addition, efforts to replenish these resources have not been sufficient enough to ensure their sustainability; thus the share of the forestry subsector has been extremely low. However, as forest depletion took place over time, rural agrarian poverty in Nigeria declined, due to the release of additional land that became available for crop and livestock production, thereby signifying the prevalence of a deep-rooted dichotomy between forest and agriculture in the country. The study recommends the replenishment of lost forest cover across the country, discouraging the primitive practice of shifting agriculture, ensuring balanced development to check rural urban drift, and the development of a national accounting system for the efficient management of forest resources.